Experimental Study on Cold Storage Characteristics of Water-cooled Compressed CO2 Hydrate Cold Storage System - Yan Kun; Xie Yingming; Zhuang Yaqi; Zou Junhua; Yang Wenyu; Shu Sheng (Zhileng xuebao)
A water-cooled compressive CO2 hydrate cold storage system was designed to examine the hydrate cold storage characteristics with different initial charge pressure values (from 3.5 MPa to 4.0 MPa). Furthermore, cold storage capacity and cold storage velocity are calculated based on the experimental data. The results indicated that as the initial charge pressure increases, the cold storage characteristics are improved. This is because as the initial charge pressure increases, the dryness degree of CO2 at the reactor inlet decreases and the cold capacity of the unit mass CO2 increases. When the initial charge pressure was 4.0 MPa, the cold storage characteristics were optimal: the cold storage time was the shortest (11.33 min), the average cold storage velocity was the highest (5.19 kW), the hydrate generating mass was of the maximum value (3.96 kg), and the ratio of hydrate cold storage capacity to total cold storage capacity was the highest (57%). When the initial charge pressure was 3.5 MPa, the cold storage characteristics were the worst: the cold storage time was the longest (37.50 min), the average cold storage velocity was the lowest (1.07 kW), the hydrate generating mass was of the minimum value (1.58 kg), and the ratio of hydrate cold storage capacity to total cold storage capacity was the lowest (34%). When compared with air-cooled compressive cold storage system, the cold storage characteristics of the water-cooled compressive cold storage system were significantly improved: the maximum increase in hydrate formation mass was 38.6%, and the maximum increase in total cold storage was 13.24%.